Organizations : behavior, structure, processes - Gibson, James L. (McGraw-Hill Irwin, 2009)
"Organizations: Behavior, Structure, Processes is steeped in the belief that the most successful managers in the global economy will be those who can anticipate, adapt, and manage change. Throughout the text, the authors have integrated current topics and research to make sure the Thirteenth Edition reflects the world that students will soon enter and learn how to effectively manage organizational behavior in an ever-changing environment."--Jacket